Impact of Maternal Education on the Intensity and Timeliness of Antenatal Care Utilization in Niger - Thonaeng Charity Molelekoa; Abayomi Samuel Oyekale (Research Synergy Foundation, 2025)
Inadequate access to antenatal care (ANC) is a public health problem promoting maternal and child mortality in many developing countries. In Niger, the utilization of ANC is a requirement for achieving some of the targets of the third Sustainable Development Goal (SDG3). This study analyzed the impact of maternal education on the intensity and timeliness of ANC use. The data were drawn from the 2021 Malaria Indicator Survey (MIS). Data were analyzed using an exponential mean model, and regression adjustment Average Treatment Effect (ATE)/ Average Treatment Effect on the Treated (ATET) estimators. The results showed that 68.66% of the women attended ANC three or four times, whereas 48.58% did not visit health centers up to four times. Only 27.09% of pregnant women attended ANC during the first trimester. The results from Poisson regression showed that ANC visits significantly increased with women’s age, education levels, urban residence, listening to radio, wealth index, and use of Fasidar medication. Moreover, the first ANC pregnancy month was associated with the women’s age, education level, and wealth index. The ATEs and ATETs were positive for ANC use intensity and negative for use timeliness, respectively. It was recommended that efforts to promote ANC use in Niger should, among others, promote maternal education through media programs.